Experiências de recuperação florestal praticadas por agricultores familiares do Nordeste do Pará - CARNEIRO, Renan do Vale (Universidade Federal do Pará, 2019)
Family farmers in Pará's Northeast traditionally develop forest recovery practices in their lots, and more recently have been adapting them. This research aimed to analyze the experiences that have been carried out by these subjects and understand the major challenges and ongoing processes. Therefore, the research was based on principles of transdisciplinarity and the sys-temic approach, and thus carried out a survey of 60 experiences in four municipalities of the northeastern mesoregion of Pará: Captain Poço, Irituia, Bragança and Tomé-Açu. In the first article, from the realization of a forest recovery typology the peculiarities of these experiences were understood, highlighting the farmers' perceptions and motivations. Thus were found the five main types of forest recovery practiced by the region's family farmers: natural regenera-tion, agroforestry backyard and the three types of agroforestry systems (poorly diversified, diversified and highly diversified). The second article, from field research, spatial analysis and secondary data, verified the integration of the practices that have been carried out by farmers and that possibilized the amplification of forest recovery scales in some specific re-gions, and the public policies that have acted in the region, with greater or less efficiency. The third article analyzes, under a space-time perspective, the diversity of trajectories that involve the processes of forest recovery practiced by family farmers. A pattern was found in the tra-jectories studied, where farmers' production systems initially undergo a process of land use intensification, then reach a crisis peak and, from there, a process of productive diversification begins, in search of the valorization of the already open lands. The results helped to conclude that the forest recovery practiced by family agriculture in the Northeast of Pará has traces of traditional but also innovative practices, thus signaling an ascending scenario of changes. There is also a confluence of motivations, which has encouraged these farmers to develop this type of practice, either through values unique of those subjects or from public performance regarding environmental problems. And so, the local scenario, therefore, inspired by social, environmental and economic paradigms, seems to point new productive paths to the Eastern Amazon.